(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
“Friso” and “Palimpsesto” or two poems published in literary magazines in Spain and Latin America about 1892 that later appeared in the first edition of Prosas Profanas In a section entitled “Recreaciones arqueológicas”. Placed after the Prosas Profanas se texts are part of discursive totality and, if we refer to the original title of the book, Prosas Profanas y otros poemas (“profane prose texts and other poems”), it can be said that “Recreaciones arqueologicas” belong to “the other poems”. Therefore this article analyses “Recreaciones…” from a unified perspective in which elements and strategies common to both are emphasized: the mythological themes, the relationship between the poetic task and other arts, and the literary genealogy of questions and procedures.